Early integration of palliative care into oncological care: a focus on patient-important outcomes. (2nd August 2022) - Ansatbayeva, Tolganay; Kaidarova, Dilyara; Kunirova, Gulnara; Khussainova, Ilmira; Rakhmetova, Venera; Smailova, Dariga; Semenova, Yuliya; Glushkova, Natalya; Izmailovich, Marina
Abstract : Background: Globally, cancer remains one of the leading causes of mortality. Palliative care is designed to meet a range of cancer patients' priority issues, including the management of pain and other cancer-associated symptoms. Routine palliative care envisages the provision of not just medical therapy, but also psychological support, social support and spiritual assistance. What constitutes the best model for palliative care remains a matter of debate. Aim: This review was undertaken with the aim to discuss different aspects of early integration of palliative care into oncological care, with a focus on patient-important outcomes. Methods: A comprehensive search of publications was conducted with a focus on integrative palliative care for incurable cancer patients. For this purpose, the following databases and search engines were used: Scopus, PubMed, Cochrane Library, Research Gate, Google Scholar, eLIBRARY and Cyberleninka. Results: A comprehensive approach with early integration of different medical services appears to be the most promising. Integrative palliative care is best provided via specialised interdisciplinary teams, given that all members maintain systemic communications and regularly exchange information. This model ensures that timely and adequate interventions are provided to address the needs of patients. Conclusion: Further research is needed to pinpoint the most optimal strategies to deliver palliative care and make it as tailored to the patient's demands as possible.